Accounting Students’ Interest in the Auditing Profession in the Digitalization Era - Setiawan, Santy; Tin, Se; Meythi, Meythi (Institut Bisnis dan Informatika Kesatuan, 2025)
The public accounting profession is considered a promising career path, as many companies continue to require public accountants to review their financial statements. This profession has also attracted the attention of accounting graduates and is among the preferred career choices. This study aims to examine gender differences in accounting students’ interest in the profession and the digital skills required to become an accountant. The research method used is a t-test to analyze gender-based differences in interest toward the auditing profession, and qualitative data to explore the digital competencies needed by accounting graduates. The findings indicate that there is no gender-based difference in interest in the auditing profession, and accounting software training is necessary to support graduates in the job market. Keywords: audit profession, digitalization, and gender.